(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present paper will analyse the concepts of faith, morality and fascism that emerge so strongly within this novel The Prime of Miss Jean Brodie. According to ancient tradition, St. Peter, the chief apostle of Christ founded the Christian Church at Rome. The Church believes that in matters of faith and morals, the teachings of the Church are infallible. This means that they are free from all possibility of error. It thereby follows that when the Pope, speaking in his apostolic capacity, makes a pronouncement in matters of faith and morals, his teaching is also infallible. Moral disarray is conveyed through the strong presentation of Miss Brodie in touching manner. She tries her level best to wield moral power and control over the destinies of others significantly but her religious sensibility fails to provide her with a clear moral perspectives. The falsehood of Miss Brodie’s claims is revealed in their documented fantasies and in their minds which are filled with her preoccupations. Her admiration for Hitler and Mussolini further supplement her image as an ideologue of fascism. Her betrayal and crushing defeat becomes inevitable. Finally, the defeat of fascism and the protagonist, Miss Brodie go together side by side, placing the novel The Prime of Miss Jean Brodie within the historical space that it seeks reflect and portray.